Survey of Underhand Passing Ability of CKM Dendang Volleyball Team - ,, Ratu; Mardian, Roli; Setiawan, Iwan Budi (Jurnal Pendidikan Jasmani (JPJ), 2025)
Abstract The problem raised in this study is how the CKM Dendang volleyball team's underhand passing ability is. This study aims to determine the underhand passing ability of the CKM Dendang volleyball team. The method used in this study is a survey method with data collection techniques using the Brumbach Forearms Pass Wall Volley Ball volleyball underhand passing test from the American VolleyBall Coaches Association (AVCA). The population in this study were 15 CKM Dendang team players, taken using the total sampling technique. Data analysis used descriptive analysis expressed in the form of percentages. The results showed that the passing ability of the CKM Dendang team showed results in the very good category with a percentage of 0%, a good category with a percentage of 7 people with a percentage of 46.67%, a sufficient category with a percentage of 46.67%, a less than adequate category with a percentage of 26.67%, and a very poor category with a percentage of 0%.